Evaluation of the effectiveness of natural stone surface treatment from Ukraine by mechanical and chemical methods (Rudarsko-geološko-naftni zbornik, 2018)
Studies have been conducted with the aim of studying ways to improve the decorative properties of natural stone products. That will allow to make finished product run of natural stone with a homogeneous tint. For this purpose, the indicators of luster, lightness and saturation of natural surfaces of facing stone worked by mechanical and chemical methods are described. The influence of chemical treatment on the decorative indicators of various kinds of natural facing stone depending on its mineralogical composition is determined.